Sublithospheric and lithospheric diamonds from the Candle Lake C29/30 kimberlite, Sask Craton - Andrea Pezzera; Fabrizio Nestola; Richard A. Stern; Aleksey Agashev; Perry Ksyniuk; Thomas Stachel; D. Graham Pearson (Lithos, 2026)

National-scale river water quality in the Philippines: establishing baselines in a mineralised megadiverse nation - Emma Biles; Richard David Williams; Decibel Faustino-Eslava; Loucel Cui; Francis Ian Gonzalvo; Kim Bryan Cabrera; Manilyn Casa; Craig MacDonell; Maria Regina V. Regalado; Laura Quick; Justine Perry Domingo; Trevor Hoey; et al. (Science of The Total Environment, 2026)

Bridging the Gap: Enhancing Prostate Cancer Survivorship and Advocacy Among Ethnically Diverse Black Men Through Community Town Halls - Motolani E. Ogunsanya; Ernest Kaninjing; Sara M. DeForge; Daniel J. Morton; Perry Cole; Patrick Beckford; Donald Reese; Thomas Mitchell; Everett Montgomery; Roland Odeleye; Erick Y. Miró-Rivera; Kaitlin Roberts; et al. (Journal of Cancer Education, 2025)
We present findings from town hall meetings held with ethnically diverse Black prostate cancer (CaP) survivors in 2022 and 2023. Four town halls (total participants, N = 265) focused on diagnosis, treatment, psychosocial support, and overall survivorship. Moderated by a long-term CaP survivor, each session featured a panel that included medical providers (urologic oncologists and clinical psychologists), as well as CaP survivors of American, Caribbean, and African origin and their spouses. Surveys captured demographic data, clinical information, CaP-specific details (for survivors only), and perceptions of the town halls. The meetings highlighted three interrelated themesinfluencing decision-making: access to comprehensive information, the strength of support networks, and the availability of culturally competent care. These town halls revealed important educational and support opportunities for ethnically diverse Black men with CaP, promoting informed decision-making throughout the cancer journey and improving quality of life while reducing decisional regret during survivorship.

Unravelling the novel mode of action of the spinosyn insecticides: A 25 year review - Trent Perry; Frank J. Wessels; Samantha Griffin; Chaoxian Geng; Natalie C. Giampietro; David G.J. Mann; Thomas C. Sparks (Pesticide Biochemistry and Physiology, 2025)

Development and Preliminary Evaluation of a Food Literacy Measure for Use With Young People in Canada - Tracey Borland; Michael D.T. Fung; Emily Taylor; Michael Chaiton; Robert Schwartz; Heather Thomas; Elsie Azevedo Perry; H. Ruby Samra; Lucy Valleau; Sharon I. Kirkpatrick (Journal of the Academy of Nutrition and Dietetics, 2025)

Play and peril: Displacement drivers and types across recreation motivations in crowding and wildfire-prone southern California national forests - Alyssa S. Thomas; Erin E. Budzyn; Elizabeth E. Perry; Brian A. Peterson; José J. Sánchez (Journal of Outdoor Recreation and Tourism, 2025)

Estimating coral reef carbonate budgets using Structure-from-Motion photogrammetry - Hannah C. Barkley; Ariel A. Halperin; Damaris Torres-Pulliza; Mia S. Lamirand; Courtney S. Couch; Candace E. Alagata; Rebecca M. Weible; Joy N. Smith; Thomas A. Oliver; Chris T. Perry (Coral Reefs, 2025)

Spinosyn resistance and cross-resistance – A 25 year review and analysis - Thomas C. Sparks; Frank J. Wessels; Trent Perry; Michael J. Price; Melissa W. Siebert; David G.J. Mann (Pesticide Biochemistry and Physiology, 2025)

Estimating Spatially Explicit Survival and Mortality Risk From Telemetry Data With Thinned Point Process Models - Joseph M. Eisaguirre; Madeleine G. Lohman; Graham G. Frye; Heather E. Johnson; Thomas V. Riecke; Perry J. Williams (Ecology Letters, 2025)
Mortality risk for animals often varies spatially and can be linked to how animals use landscapes. While numerous studies collect telemetry data on animals, the focus is typically on the period when animals are alive, even though there is important information that could be gleaned about mortality risk. We introduce a thinned spatial point process (SPP) modelling framework that couples relative abundance and space use with a mortality process to formally treat the occurrence of mortality events across the landscape as a spatial process. We show how this model can be embedded in a hierarchical statistical framework and fit to telemetry data to make inferences about how spatial covariates drive both space use and mortality risk. We apply the method to two data sets to study the effects of roads and habitat on spatially explicit mortality risk: (1) VHF telemetry data collected for willow ptarmigan in Alaska, and (2) hourly GPS telemetry data collected for black bears in Colorado. These case studies demonstrate the applicability of this method for different species and data types, making it broadly useful in enabling inferences about the mechanisms influencing animal survival and spatial population processes while formally treating survival as a spatial process, especially as the development and implementation of joint analyses continue to progress.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Analysis of nonsynonymous SNPs in candidate genes that influence bovine temperament and evaluation of their effect in Brahman cattle - Gilberto Ruiz-De-La-Cruz; Ana María Sifuentes-Rincón; Francisco Alejandro Paredes-Sánchez; Gaspar Manuel Parra-Bracamonte; Eduardo Casas; David G. Riley; George A. Perry; Thomas H. Welsh; Ronald D. Randel (Molecular Biology Reports, 2024)
Background Temperament is an important production trait in cattle and multiple strategies had been developed to generate molecular markers to assist animal selection. As nonsynonymous single nucleotide polymorphisms are markers with the potential to affect gene functions, they could be useful to predict phenotypic effects. Genetic selection of less stress-responsive, temperamental animals is desirable from an economic and welfare point of view. Methods and results Two nonsynonymous single nucleotide polymorphisms identified in HTR1B and SLC18A2 candidate genes for temperament were analyzed in silico to determine their effects on protein structure. Those nsSNPs allowing changes in proteins were selected for a temperament association analysis in a Brahman population. Transversion effects on protein structure were evaluated in silico for each amino acid change model, revealing structural changes in the proteins of the HTR1B and SLC18A2 genes. The selected nsSNPs were genotyped in a Brahman population ( n = 138), and their genotypic effects on three temperament traits were analyzed: exit velocity, pen score, and temperament score. Only the SNP rs209984404-HTR1B (C/A) showed a significant association ( P = 0.0144) with pen score. The heterozygous genotype showed a pen score value 1.17 points lower than that of the homozygous CC genotype. Conclusion The results showed that in silico analysis could direct the selection of nsSNPs with the potential to change the protein. Non-synonymous single nucleotide polymorphisms causing structural changes and reduced protein stability were identified. Only rs209984404-HTR1B shows that the allele affecting protein stability was associated with the genotype linked to docility in cattle.

Revealing the palaeoecology of silent taxa: selecting proxy species from associations in modern vegetation data - Jacqui M. M. Vanderhoorn; Janet M. Wilmshurst; Sarah J. Richardson; Thomas R. Etherington; George L. W. Perry (Journal of Biogeography, 2024)
Aim Species severely under‐represented in fossil pollen records leave gaps in interpretations and reconstructions of past vegetation. These ‘silent taxa’ leave little or no trace due to low pollen production, dispersal, preservation and taxonomic resolution. An approach for including them is through associating them with other species with reliable pollen representation. Here, we demonstrate a method for selecting such a proxy species for the Holocene using modern vegetation data. Location New Zealand. Taxon Beilschmiedia tawa (A.Cunn.) Benth. & Hook. F. ex Kirk (Lauraceae). Methods We used vegetation plot data to perform a pairwise co‐occurrence analysis of the New Zealand indigenous forest metacommunity to identify species with a strong positive association with Beilschmiedia tawa (tawa), a common tree severely under‐recorded in the pollen record. For those species, we then modelled their realised climatic niches to identify species with high niche overlap. We discuss how well those species could be interpreted from the Holocene fossil pollen record based on the representation of their pollen taxa. Results Knightia excelsa (rewarewa; Proteaceae) is a potential proxy for B. tawa in Holocene fossil pollen records, and other, range‐limited species may provide community‐specific proxies. We show combining resampling with sub‐sampling is a robust method for reducing the high false positive rate associated with large co‐occurrence analyses (1000+ sites) by limiting the sample size to 100 sites. Main Conclusions We show that the palaeoecology of silent taxa can be studied via proxy species, allowing their past distributions to be better understood. We highlight the importance of modelling many aspects of the realised niche to understand the usefulness and limitations of the silent–proxy association. Future research should focus on testing the underlying assumptions of the silent–proxy relationship so that models built on modern data can confidently be applied to palaeoecological data.

The importance of developmental programming in the beef industry - George A. Perry; Thomas H. Welsh (Animal Reproduction Science, 2024)

Targeting and image acquisition of Martian surface features with TGO/CaSSIS - M. Almeida; M. Read; N. Thomas; G. Cremonese; P. Becerra; G. Borrini; S. Byrne; M. Gruber; R. Heyd; C.M. Marriner; G. McArthur; A.S. McEwen; et al. (Planetary and Space Science, 2023)

Electrocardiogram to Determine Mitral and Aortic Valve Opening and Closure - M. Rifqi Aufan; Zachary T. Jost; Neal J. Miller; Oleg F. Sharifov; Himanshu Gupta; Gilbert J. Perry; J. Michael Wells; Thomas S. Denney; Steven G. Lloyd (Cardiovascular Engineering and Technology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Escaping the fate of Sisyphus: assessing resistome hybridization baits for antimicrobial resistance gene capture - Megan S. Beaudry; Jesse C. Thomas; Rodrigo P. Baptista; Amanda H. Sullivan; William Norfolk; Alison Devault; Jacob Enk; Troy J. Kieran; Olin E. Rhodes; K. Allison Perry‐Dow; Laura J. Rose; Natalia J. Bayona‐Vásquez; et al. (Environmental Microbiology, 2021)
Summary Finding, characterizing and monitoring reservoirs for antimicrobial resistance (AMR) is vital to protecting public health. Hybridization capture baits are an accurate, sensitive and cost‐effective technique used to enrich and characterize DNA sequences of interest, including antimicrobial resistance genes (ARGs), in complex environmental samples. We demonstrate the continued utility of a set of 19 933 hybridization capture baits designed from the Comprehensive Antibiotic Resistance Database (CARD)v1.1.2 and Pathogenicity Island Database (PAIDB)v2.0, targeting 3565 unique nucleotide sequences that confer resistance. We demonstrate the efficiency of our bait set on a custom‐made resistance mock community and complex environmental samples to increase the proportion of on‐target reads as much as >200‐fold. However, keeping pace with newly discovered ARGs poses a challenge when studying AMR, because novel ARGs are continually being identified and would not be included in bait sets designed prior to discovery. We provide imperative information on how our bait set performs against CARDv3.3.1, as well as a generalizable approach for deciding when and how to update hybridization capture bait sets. This research encapsulates the full life cycle of baits for hybridization capture of the resistome from design and validation (both in silico and in vitro ) to utilization and forecasting updates and retirement.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Site use and connectivity of female grey seals (Halichoerus grypus) around Wales - Izzy Langley; Tobias Rosas da Costa Oliver; Lex Hiby; Thomas B. Stringell; Ceri W. Morris; Oliver O’Cadhla; Lisa Morgan; Kate Lock; Sarah Perry; Stephen Westcott; Dave Boyle; Birgitta I. Büche; et al. (Marine Biology, 2020)
Grey seals ( Halichoerus grypus ) are a qualifying feature of three special areas of conservation (SACs) in Wales, yet relatively little is known of their site use along this coastline. Since 1992, many individuals and organisations have contributed to a grey seal photographic identification database held by Natural Resources Wales, which is one of the largest and oldest of its kind, providing key information from grey seal haul-out sites around the Celtic and Irish Seas. Here, we investigated spatial connectivity of haul-out sites and fidelity of adult females to breeding sites. The minimum number of adult female grey seals using the area between 1992 and 2016 was 2688. Individual capture histories and relative spatial transition probabilities ( P ij ) between pairs of location groups were calculated. Adjacent locations were highly connected (e.g. Lleyn Peninsula and Bardsey, P ij = 0.7) but connections spanned the entire region, up to 230 km apart (e.g. Skomer and Dee Estuary, P ij = 0.004). Resights were recorded within SACs (e.g. Lleyn Peninsula and Bardsey [Lleyn Peninsula and the Sarnau SAC], P ij = 0.7), between SACs (e.g. Bardsey and Skomer [Pembrokeshire Marine], P ij = 0.03), between SACs and non-designated areas (e.g. Skerries and Bardsey, P ij = 0.09) and between sites outside any protected area (e.g. Dee Estuary and Anglesey, P ij = 0.5). While inter-annual fidelity to breeding sites was high ( P ij = 0.82–1), individual female grey seals moved throughout the region. This evidence of extensive site use beyond protected areas is important for the management and conservation of grey seals around Wales.

A randomized, placebo-controlled, phase 1 study to evaluate the effects of TAK-063 on ketamine-induced changes in fMRI BOLD signal in healthy subjects - Deborah A. Yurgelun-Todd; Perry F. Renshaw; Paul Goldsmith; Tolga Uz; Thomas A. Macek (Psychopharmacology, 2020)
Rationale Phosphodiesterase 10A inhibitor TAK-063 has shown effects that suggest efficacy in schizophrenia treatment. Objective This randomized, double-blind, placebo-controlled, incomplete-crossover study investigated effects of single oral administration of TAK-063 on ketamine-induced changes in blood oxygen level-dependent (BOLD) signal in healthy males. Methods Healthy men aged 18 to 45 years with normal magnetic resonance imaging (MRI) scans and electroencephalogram measurements at screening were eligible. Each subject was randomized to one of nine treatment schedules: all subjects received placebo and two of three doses of TAK-063 followed by ketamine. The primary endpoint was ketamine-induced brain activity in select regions of the brain during resting state. Secondary endpoints included pharmacokinetic parameters of TAK-063, proportion of subjects with treatment-emergent adverse events (AEs), and percentage of subjects meeting criteria for abnormal safety laboratory tests and vital sign measurements. Results The study comprised 27 subjects. Prior to ketamine infusion, TAK-063 exerted region-specific effects on resting state functional MRI (fMRI) BOLD signal. After ketamine administration, TAK-063 reduced the Cohen’s effect size for resting-state fMRI BOLD signal in key brain regions examined, and exerted similar effects on BOLD signal during the working memory task across all doses. TAK-063 was safe and well tolerated. Conclusions Our results are consistent with non-clinical studies of ketamine and TAK-063 and clinical studies of ketamine and risperidone. It is unknown whether these data are predictive of potential antipsychotic efficacy, and further analyses are required.

Cerebrovascular haemodynamics during isometric resistance exercise with and without the Valsalva manoeuvre - Blake G. Perry; Tom De Hamel; Kate N. Thomas; Luke C. Wilson; Travis D. Gibbons; James D. Cotter (European Journal of Applied Physiology, 2020)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Lead poisoning from ingestion of fishing gear: A review - Tiffany Grade; Pamela Campbell; Thomas Cooley; Michelle Kneeland; Elaine Leslie; Brooke MacDonald; Julie Melotti; Joseph Okoniewski; Elizabeth Jane Parmley; Cyndi Perry; Harry Vogel; Mark Pokras (Ambio, 2019)

Developing a Social–Ecological–Environmental System Framework to Address Climate Change Impacts in the North Pacific - Steven J. Bograd; Sukyung Kang; Emanuele Di Lorenzo; Toyomitsu Horii; Oleg N. Katugin; Jackie R. King; Vyacheslav B. Lobanov; Mitsutaku Makino; Guangshui Na; R. Ian Perry; Fangli Qiao; Ryan R. Rykaczewski; et al. (Frontiers in Marine Science, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Habitat Connectivity of Fish in Temperate Shallow-Water Seascapes - Diana Perry; Thomas A. B. Staveley; Martin Gullström (Frontiers in Marine Science, 2018)

Twenty years of ModelDB and beyond: building essential modeling tools for the future of neuroscience - Robert A. McDougal; Thomas M. Morse; Ted Carnevale; Luis Marenco; Rixin Wang; Michele Migliore; Perry L. Miller; Gordon M. Shepherd; Michael L. Hines (Journal of Computational Neuroscience, 2017)

Hybrid plants preserve unique genetic variation in the St Helena endemic trees Commidendrum rotundifolium DC Roxb. and C. spurium (G.Forst.) DC - Alan Gray; Annika Perry; Stephen Cavers; Antonia Eastwood; Michelle Biermann; Andrew Darlow; Vanessa Thomas; Phil Lambdon (Conservation Genetics, 2017)

Positive Feedbacks to Fire-Driven Deforestation Following Human Colonization of the South Island of New Zealand - Alan J. Tepley; Thomas T. Veblen; George L. W. Perry; Glenn H. Stewart; Cameron E. Naficy (Ecosystems, 2016)

Density‐dependent resource selection by a terrestrial herbivore in response to sea‐to‐land nutrient transfer by seals - Philip D. McLoughlin; Kenton Lysak; Lucie Debeffe; Thomas Perry; Keith A. Hobson (Ecology, 2016)
Sea‐to‐land nutrient transfers can connect marine food webs to those on land, creating a dependence on marine webs by opportunistic species. We show how nitrogen, imported by gray seals, Halichoerus grypus , and traced through stable isotope (δ 15 N) measurements in marram grass , Ammophila breviligulata , significantly alters foraging behavior of a free‐roaming megaherbivore (feral horses, Equus ferus caballus ) on Sable Island, Canada. Values of δ 15 N correlated with protein content of marram and strongly related to pupping‐seal densities, and positively influenced selective foraging by horses. The latter was density dependent, consistent with optimal foraging theory. We present the first demonstration of how sea‐to‐land nutrient transfers can affect the behavioral process of resource selection (resource use relative to availability) of terrestrial consumers. We hypothesize that persistence of horses on Sable Island is being facilitated by N subsidies. Our results have relevance to advancing theory on trophic dynamics in island biogeography and metaecosystem ecology.

Phenotypic variation and identification of quantitative trait loci for ozone tolerance in a Fiskeby III × Mandarin (Ottawa) soybean population - Amy L. Burton; Kent O. Burkey; Thomas E. Carter; James Orf; Perry B. Cregan (Theoretical and Applied Genetics, 2016)

Confirmation of delayed canopy wilting QTLs from multiple soybean mapping populations - Sadal Hwang; C. Andy King; Jeffery D. Ray; Perry B. Cregan; Pengyin Chen; Thomas E. Carter; Zenglu Li; Hussein Abdel-Haleem; Kevin W. Matson; William Schapaugh; Larry C. Purcell (Theoretical and Applied Genetics, 2015)

A genetic discontinuity in moose (Alces alces) in Alaska corresponds with fenced transportation infrastructure - Robert E. Wilson; Sean D. Farley; Thomas J. McDonough; Sandra L. Talbot; Perry S. Barboza (Conservation Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Follicular determinants of pregnancy establishment and maintenance - Ky G. Pohler; Thomas W. Geary; Jacqueline A. Atkins; George A. Perry; Emma M. Jinks; Michael F. Smith (Cell and Tissue Research, 2012)

Pacific Rim Forestry - Thomas Brandeis; Olaf Kuegler; Robert Pattison; Örjan Jonsson; James Halperin; Kathleen McGinely; Constance Carpenter; Kathleen Friday; Guy Robertson; Nicklos Dudley; Robert James; Richard Sniezko; et al. (Journal of Forestry, 2011)
68Stakeholders' questions about subtropical and tropical forests can be as diverse and unique as the forests themselves. Obtaining the information needed to begin answering these questions requires innovation and adaptation of existing forest mensuration and inventory techniques that were developed primarily for use in temperate and boreal forests with a strong forest industry presence. Five cycles of forest inventory and monitoring in Puerto Rico and two cycles in the US Virgin Islands under the Forest Inventory and Analysis (FIA) program highlight the commonalities and differences between working in these subtropical forests and the temperate forests of the continental United States. Additionally, the Caribbean implementation of the FIA program has often taken a different approach from that used in the Pacific Islands territories. We can improve on delivery of forest resource information to island stakeholders by studying these experiences. By sharing the lessons learned with other Pacific Rim countries engaging in forest inventory and monitoring, we can learn from each other.

Mercury in breeding saltmarsh sparrows (Ammodramus caudacutus caudacutus) - Oksana P. Lane; Kathleen M. O’Brien; David C. Evers; Thomas P. Hodgman; Andrew Major; Nancy Pau; Mark J. Ducey; Robert Taylor; Deborah Perry (Ecotoxicology, 2011)

Assessing Potential Risk to Alligators, Alligator mississippiensis, from Nutria Control with Zinc Phosphide Rodenticide Baits - Gary W. Witmer; John D. Eisemann; Thomas M. Primus; Jeanette R. O’Hare; Kelly R. Perry; Ruth M. Elsey; Phillip L. Trosclair (Bulletin of Environmental Contamination and Toxicology, 2010)

Immobilizing nitrogen to control plant invasion - Laura G. Perry; Dana M. Blumenthal; Thomas A. Monaco; Mark W. Paschke; Edward F. Redente (Oecologia, 2010)

Microbial degradation of usnic acid in the reindeer rumen - Monica A. Sundset; Perry S. Barboza; Thomas K. Green; Lars P. Folkow; Arnoldus Schytte Blix; Svein D. Mathiesen (The Science of Nature, 2010)

The effects of cannabinoids on serum cortisol and prolactin in humans - Mohini Ranganathan; Gabriel Braley; Brian Pittman; Thomas Cooper; Edward Perry; John Krystal; Deepak Cyril D’Souza (Psychopharmacology, 2009)

Enhancing functional expression of heterologous lipase in the periplasm of Escherichia coli - Yali Xu; Amrita Yasin; Thomas Wucherpfennig; C. Perry Chou (World Journal of Microbiology and Biotechnology, 2008)

Effects of haloperidol on the behavioral, subjective, cognitive, motor, and neuroendocrine effects of Δ-9-tetrahydrocannabinol in humans - Deepak Cyril D’Souza; Gabriel Braley; Rebecca Blaise; Michael Vendetti; Stephen Oliver; Brian Pittman; Mohini Ranganathan; Savita Bhakta; Zoran Zimolo; Thomas Cooper; Edward Perry (Psychopharmacology, 2008)

Predicting Cotton Lint Yield Maps from Aerial Photographs - G. Vellidis; M. A. Tucker; C. D. Perry; D. L. Thomas; N. Wells; C. K. Kvien (Precision Agriculture, 2004)